Implications of the Law of Religious Moderation on Interfaith Marriages - Gunawan, Edi; Tohis, Reza Adeputra; Hakim, Budi Rahmat (IAIN Manado, 2023)
This research examines the implications of religious moderation on interfaith marriages in the city of Manado. The method used is qualitative with a case study approach; data collection is through observation, interviews, and documentation, which is then processed using the triangulation method. The findings show that religious moderation indirectly influences the sustainability of interfaith marriages in Manado. The implications are realized in the form of religious moderation, which aims to eliminate or minimize violence in the name of religion and uphold diversity through upholding the values of tolerance, thereby increasing guarantees for the continuity of interfaith marriages. These implications become more complex than the laws governing interfaith marriages, especially the Marriage Law (UU Number 16 of 2019) and the Compilation of Islamic Law (KHI). The implications of religious moderation in interfaith marriages underscore the need for legal transformation that recognizes religious diversity as a social asset, encourages interreligious dialogue, and ensures that legal regulations do not hinder individual religious freedom. Encouraging policy reforms that respect differences in beliefs is crucial in creating inclusive spaces and respecting human rights in interfaith marriages.